EU Regulatory and Technical Foundations for Construction Materials: Economic Rationale for Integrating Standards and Regulations into Architectural and Construction Projects - Mykhalko, Anastasiia; Kubanov, Ruslan; Denysiuk, Olga; Makatora, Dmytro (ІНЖЕК, 2025)
The article examines the regulatory and technical foundations for the use of construction materials in the European Union and substantiates the economic efficiency of integrating European standards and regulations into the activities of Ukrainian architectural and construction companies. It is shown that the contemporary development of the sector takes place under conditions of deep integration into the European economic space; however, a gap remains between the existing national standards and EU requirements. This gap complicates the entry of Ukrainian companies into the international market and reduces their competitiveness. The article analyses the evolution of European construction policy, beginning with the “New Approach” of 1985, which laid the foundations for simplifying access to the internal market and for the transition from detailed technical specifications to essential requirements. It is determined that the subsequent “Global Approach” complemented these principles by focusing on conformity assessment of products against standards. This created favourable conditions for innovation, the development of a competitive environment, and the formation of a unified system of requirements for construction materials. Particular attention is paid to key EU standards: EN Eurocodes (EN 1990–1999), EU Regulation No. 305/2011 (CPR), EN 206 (Concrete), EN 771 (Masonry Units), EN 13163 (Thermal insulation products), EN 14081 (Timber structures), EN 1090 (Steel structures), EN 15804 (Environmental Product Declarations), and EN 13501 (Fire classification). These standards define requirements for strength, durability, energy efficiency, environmental performance, and the safety of construction materials. For Ukrainian companies, their implementation signifies not only an improvement in product quality but also access to the European market, participation in international tenders, and the formation of a positive corporate image. The article presents examples of harmonisation of EU standards with Ukrainian DSTU standards, which already cover concrete, masonry products, thermal insulation, timber, steel, fire safety, and environmental declarations. At the same time, it is emphasised that the process of adapting the Eurocodes and the CPR remains incomplete and requires a systemic approach. The absence of a unified roadmap for standards integration leads to fragmented actions by companies that do not always recognise the strategic benefits of certification, CE marking, or environmental declarations. The methodological framework of the study is based on systemic, comparative, and economic-analytical approaches. The research employs methods of content analysis of regulatory documents, expert assessments, and case studies to examine practical examples of harmonisation. Statistical analysis of data on the implementation of EN 206, EN 771, EN 1090, and EN 15804 was applied, making it possible to quantitatively assess the effectiveness of their use. The results of the study demonstrate that the integration of EU standards into the activities of Ukrainian architectural and construction companies provides four key advantages: technical quality (durability and safety of structures), customer trust (process transparency, CE marking, environmental declarations), market access (participation in international tenders and projects), and economic benefits (reduced maintenance costs, resource optimisation, compliance with ESG requirements). Thus, EU standards function not only as a formal regulatory requirement but also as a strategic development instrument that enables Ukrainian companies to operate confidently, transparently, and efficiently in both domestic and external markets. The implementation of these standards is economically sound, reputationally advantageous, and strategically necessary for the sustainable development of Ukraine’s construction industry in the context of European integration.
Нормативно-технічні основи використання будівельних матеріалів в ЄС: обґрунтування економічної ефективності інтеграції стандартів і регламентів у проєктній діяльності архітектурно-будівельної компанії
Keywords: European standards (EN, Eurocodes, CPR), fire safety (EN 13501); harmonisation of DSTU and EN; construction materials; economic efficiency; CE marking; environmental declarations (EPD, EN 15804); building energy efficiency; architectural and construction companies; project activities; project management; international tenders; competitiveness; integration into the EU market; європейські стандарти (EN, Eurocodes, CPR); гармонізація ДСТУ та EN; будівельні матеріали; економічна ефективність; екологічні декларації (EPD, EN 15804); CE-маркування; пожежна безпека (EN 13501); енергоефективність будівель; архітектурно-будівельні компанії; управління проєктами; проєктна діяльність; інтеграція до ринку ЄС; конкурентоспроможність; міжнародні тендери; 691:006.83]:338.45